Faculty and international student perceptions of language performance and instructional support: A mismatch of expectations. Issue 1 (24th May 2019) - Gallagher, Colleen; Haan, Jennifer; Lovett, Sarah
Abstract : With increasingly mobile and global populations in universities worldwide, it is important that faculty and students share common expectations for student and instructor behaviors. This study focused on international student and faculty perceptions of student language performance and faculty instructional techniques in one U.S. university with recent growth in the international student population. Using responses from two questionnaires administered to faculty and matriculated international students at the university, the authors found a mismatch between faculty and student perceptions. Faculty rated students' linguistic performance poorly, whereas students saw their language skills as adequate for the demands of their classes. In terms of instructional supports for international students, both students and faculty reported using or appreciating visuals, but other strategies such as advance provision of instructional materials or invitations to office hours were appreciated by students but less often used by faculty. The authors discuss the results in terms of developing shared expectations between students and faculty and engaging in intentional language acquisition planning at the institutional level.